Shrinking possibilities. - Arnold, B.
Lithography will need multiple strategies to keep up with the evolution of memory and logic.
Keywords: EUV lithography; Extreme ultraviolet lithography; Lithography; Logic evolution; Memory evolution; Optical lithography; Semiconductor industry